Mathematical modelling and compensation strategies for printing dot gain - Xiaoli Liu; Bingzhong Qiu; Ying-Leh Ling (PLoS ONE, 2025)
In contemporary printing processes, dot gain is a pivotal factor influencing print quality. This phenomenon, characterized by the loss of image details and the potential for chromatic aberration, poses significant challenges to enhancing print quality. Despite extensive research that has been conducted by numerous scholars on dot gain, effective control and correction of this phenomenon in practical printing operations remain an urgent concern. This study utilized newsprint, offset paper, and coated paper as research objects, and employed the least squares method and MATLAB tools to calculate dot gain compensation values through the “coordinate transformation method” and fit the compensation curve of dot gain. The novelty of this research lies in its development of an integrated mathematical modeling approach that combines least squares optimization with coordinate transformation, providing a computationally efficient alternative to traditional inverse function methods. The experimental results demonstrated that the compensation strategy was effective in the mid-tone and dark-tone areas, significantly enhancing printing accuracy and stability. However, in the bright tone area, further optimization of the compensation effect is necessary. The study proposes a dot gain compensation strategy based on the least squares method, providing the printing industry with new ideas and technical support for enhancing printing quality.